Cubic–quartic optical soliton perturbation with complex Ginzburg–Landau equation by the enhanced Kudryashov's method. (February 2022) - Arnous, Ahmed H.; Biswas, Anjan; Yıldırım, Yakup; Zhou, Qin; Liu, Wenjun; Alshomrani, Ali S.; Alshehri, Hashim M.
Highlights: A cubic–quartic complex Ginzburg–Landau equation is studied. The enhanced Kudryashov's method is applied. Bright and singular solitons are recovered for this model. Abstract: This paper implements the enhanced Kudryashov's method to address cubic–quartic complex Ginzburg–Landau equation for locating its solitons. This is considered when chromatic dispersion is discarded because of its low count. Sis forms of self-phase modulation structures are studied and they are Kerr law, parabolic law, polynomial law, quadratic–cubic law, anti-cubic law and parabolic-nonlocal law. Thus, bright and singular solitons are recovered for this model. The existence criteria for such solitons have been indicated, as well.